Islamic Movements of Europe : Public Religion and Islamophobia in the Modern World - Edited by Peter, Frank and Ortega, Rafael (London I.B. Tauris, 2013)
Featuring the work of more than 40 scholars, this is the comprehensive guide to Islam in Europe and will be essential reading for policy-makers, political commentators and academics working with Islamic groups in Europe.
Keywords: Islamophobia -- Islam and politics